The impact of childhood adversity on female-perpetrated intimate partner violence in young adulthood - McGrath, Ailsa (Legal and criminological psychology, 2024)
Purpose A common conception of intimate partner violence (IPV) is that women rarely use violence against romantic partners, and when they do, this is usually in self-defence. However, evidence demonstrates that women perpetrate IPV at least as frequently as men, particularly in young adult populations. Despite this, there is still a significant lack of research focusing on women's IPV perpetration, particularly in determining risk markers. The unique relationship between adversity in childhood and IPV perpetration has been recognized in males and it is thought that this relationship may be even more marked in females. The present study aimed to investigate this relationship to see whether experiencing increasing numbers of adverse childhood experiences (ACEs) would be associated with higher incidence of female-perpetrated IPV. Methods Exposure to ACEs and frequency of IPV perpetration was measured through an online survey of young adult females from the general population. Results Regression analysis revealed that ACEs did significantly predict the frequency of IPV perpetrated by females. The results showed that the more adversity a female has experienced in childhood, the greater their risk of IPV perpetration in young adulthood. Conclusions It is suggested that this relationship potentially exists because adversity in childhood impacts the individual's attachments and processing of social environments, thus resulting in dysfunctional, violent responses to relationship dilemmas throughout life. These results stress the importance of tailoring treatment strategies for female perpetrators to address potential childhood adversity in which their violence may be rooted.